Question

Exercise 6
Solve the following equation. 3(3m2)=2(3m+3)\begin{aligned} 3(3m-2)=2(3m+3) \end{aligned}

Answer

m=4m=4

Hint

Start with expanding the expressions on both sides.

Solution

We need to find the value of mm for which the two sides evaluate to the same number. We start with expanding the expressions on both sides of the equality.
3(3m2)=2(3m+3)3(3m-2)=2(3m+3)
9m6=6m+69m-6=6m+6
Next we use inverse operations to isolate m.m.
9m6=6m+69m-6=6m+6
9m6m6=69m-6m-6=6
9m6m=129m-6m=12
(96)m=12(9-6)m=12
3m=123m=12
m=4m=4
Hence, the value that makes the equality true is m=4.m=4.

{{ 'ml-template-article-upsell1' | message }}

{{ 'ml-template-article-upsell2' | message }}

{{ 'ml-template-article-upsell3' | message }}